PERBANDINGAN CERITA “MAHLIGAI KELOYANG” DAN “KOBA MALIN DEMAN” - Sri Sabakti (Balai Bahasa Provinsi Riau, 2016)
Many folklores have same motives, but different in development adjust to the community that support the story. Differences in the development of the story in folklore shows the influences of local cultures to the storyteller. The differences cause various versions of folklore. It is also seen in folklore Mahligai Keloyang from Indragiri Hulu Regency and Koba Malin Deman from Rokan Hulu Regency. Therefore, this study aimed to find the similarities and the differences of the two folklores. The analysis of the similarities and differences of The legend Mahligai Keloyang and Koba Malin Deman applied dynamic structuralism theory, the theory which does not only emphasizes the intrinsic elements, but also pay attention to extrinsic elements in literature. Due to the fact that the study was also intended to compare two folklores, the research method used is descriptive comparative method. Based on the analysis of the structure of the story, it is found that there are similarities and differences in the stories Mahligai Keloyang and Koba Malin Deman which includes elements of the theme, the characters, the settings, and the plots. Based on the analysis of the cultural values in the folklores, some similarities and differences of religious values, moral values, and social values are found.